Effectiveness of various atropine concentrations in myopia control for Asian children: a network meta-analysis - Wang, Xiaoyan; Zhang, Linyu; Gan, Jinhua; Wang, Yun; Yang, Weihua (Frontiers in Pharmacology, 2024)
ObjectivesTo assess the effectiveness of various atropine concentrations in managing myopia among children in East, South, and Southeast Asia, and to determine the most effective concentration.MethodsA systematic literature review was conducted using PubMed, Web of Science, Cochrane Library, and EMBASE. The search was limited to articles published up to 1 June 2024, and included studies in Chinese or English. Two researchers independently screened the literature, extracted relevant data, and assessed the data quality using the Revised Cochrane risk-of-bias 2 (RoB2) tool. A network meta-analysis was performed using Stata 14.2 software to compare the efficacy of different atropine concentrations in delaying myopia progression, measured by changes in refraction and axial length.ResultsThe analysis included 39 studies with 7,712 participants, examining 10 atropine concentrations ranging from 0.005% to 1%. Forest plots indicated that five concentrations (0.01%, 0.02%, 0.025%, 0.05%, and 1%) were more effective than a placebo in controlling myopia progression. The cumulative ordination plot indicated that 0.05% atropine most effectively delayed refraction change, which the mean change per year was 0.62D, while 1% was superior in slowing axial length progression, which the mean change per year was −0.43 mm. Considering both measures, 1% atropine showed the highest efficacy which the mean changes per year were 0.56D in spherical equivalent refraction and −0.43 mm in axial length, followed by 0.05% and 0.125% atropine.ConclusionWhile 1% atropine demonstrated the highest efficacy in myopia control among East, South and Southeast Asian children, its use is not recommended due to increased adverse effects and a rapid rebound in myopia after cessation. Considering both efficacy and safety, 0.05% atropine is suggested as the optimal concentration for myopia management in this population.